Accountability in Post‐Crisis Eurozone Governance: The Tricky Case of the European Stability Mechanism. (22nd March 2019) - Howarth, David; Spendzharova, Aneta
Abstract: Established at the height of the Eurozone sovereign debt crisis, the intergovernmental European Stability Mechanism (ESM) has, potentially, considerable influence over decisions on the provision of loans to Eurozone member state governments and on the recapitalization of banks. Legally and organizationally, the ESM is an international financial institution and thus its accountability can be compared to that of the International Monetary Fund (IMF) and other international financial institutions. However, the ESM's governance structure and decision‐making procedures show that it is deeply embedded in the Eurozone governance architecture, resulting in a dual institutional embeddedness. Focusing on vertical and horizontal accountability combined with a learning perspective on accountability, this article presents an assessment of the accountability mechanisms applicable to the idiosyncratic ESM and how these mechanisms work in practice.